Resin coated ultra-thin glass and display device
By forming a three-layer resin coating layer on ultra-thin plate glass and using a combination of thermoplastic resin and silicone resin, the problem of difficulty in balancing impact resistance, bending resistance and high transparency in the existing technology is solved. Better glass performance achieved.
Patent Information
- Application Number
- CN202180087568.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-29
- Filing Date
- 2021-12-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-12-16
AI Technical Summary
The prior art is difficult to improve the bending resistance of foldable devices while maintaining high transparency and impact resistance, especially in applications of ultra-thin sheet glass.
A three-layer structure of resin-coated ultra-thin plate glass is used. One side forms an organic film composed of thermoplastic resin, and the other side forms an organic film composed of silicone resin. These resin layers improve the impact resistance and resistance of the glass. Flexibility.
It achieves a balance of high transparency, impact resistance and bending resistance, significantly improving the overall performance of ultra-thin plate glass.
Smart Images

Figure GDA0004302978200000121 
Figure GDA0004302978200000131 
Figure GDA0004302978200000141
Abstract
Description
Technical Field
[0001] The invention relates to a resin-coated ultra-thin plate glass and a display device. Background Art
[0002] In recent years, with the advancement of display panel technology such as liquid crystal display devices and organic electroluminescence (EL) display devices, various display terminals such as wearable terminals, smartphones, and tablets have a strong demand for a display or cover glass with a distinctive shape.
[0003] Among them, research on foldable devices that are flexible and foldable is also gaining popularity.
[0004] However, foldable devices require that the cover glass used to protect the display or frame be thinned to a degree that it can be bent, and the thickness of the glass plate needs to be ultra-thin to about 0.1 mm or less (hereinafter, 0.1 mm or less is sometimes referred to as ultra-thin). Since the strength of the glass substrate depends greatly on the thickness, the ultra-thin glass substrate with a thin thickness has the problem of reduced impact resistance and the glass breaking with a slight impact. On the other hand, in order to improve the impact resistance, when the ultra-thin glass substrate is thickened, there is a problem of deterioration in bending resistance, and it is difficult to take into account both impact resistance and bending resistance.
[0005] As a technology for improving the strength of glass, a tempered glass substrate represented by "Gorilla Glass" (registered trademark) from Corning is known. This is a technology that provides a compressive stress layer on both sides of the glass by treating the glass substrate with a chemical solution or the like, thereby improving the strength of the glass compared to ordinary glass.
[0006] As another technology for improving the strength of glass, there is a technology for forming a film on a glass substrate. For example, a composite body is proposed, comprising: a glass substrate having microcracks on the surface, and a resin layer disposed on the glass substrate, wherein the resin of the resin layer enters at least a portion of the inside of the microcracks (for example, refer to Patent Document 1); a glass protective film, which is made using a composition containing a multifunctional epoxy (meth)acrylate compound, a multifunctional thiol compound, and a free radical polymerization initiator (for example, refer to Patent Document 2); a glass-reinforced substrate having a cured film containing a siloxane resin and silica particles on at least one side of the reinforced glass substrate (for example, refer to Patent Document 3); a glass-plastic composite film, comprising a glass film having a thickness between 10 μm and 500 μm, in which a polymer layer having a thickness between 1 μm and 200 μm is directly adhered to at least one of the side surfaces of the glass film (for example, refer to Patent Document 4), etc.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2015 / 194324
[0010] Patent Document 2: Japanese Patent Application Publication No. 2016-3160
[0011] Patent Document 3: Japanese Patent Application Publication No. 2019-214492
[0012] Patent Document 4: Japanese Patent Publication No. 2002-542971 Summary of the invention
[0013] Problems to be solved by the invention
[0014] Although the glass strength can be improved by strengthening the glass substrate or the techniques described in Patent Documents 1 to 4, the requirements for balancing the impact resistance and bending resistance of foldable devices have increased due to the installation of touch panels, etc., which has become a problem.
[0015] The present invention has been made in view of the above-mentioned problems of the prior art, and an object of the present invention is to provide a resin-coated ultra-thin glass plate having high impact resistance, good bending resistance, and high transparency.
[0016] Technical means of solving problems
[0017] The present inventors have conducted intensive studies to solve the problems of the prior art and have found that the following structure is extremely effective, thereby completing the present invention.
[0018] That is, the present invention is a resin-coated ultra-thin glass, comprising three layers: an organic film (B) formed on one side of an ultra-thin glass (A) having a thickness of greater than 10 μm and less than 100 μm, and an organic film (C) formed on the other side, wherein in the resin-coated ultra-thin glass, the organic film (B) is formed from a composition containing a thermoplastic resin (D) having a weight average molecular weight of 1,000 to 70,000, and the organic film (C) is formed from a composition containing a siloxane resin (E).
[0019] Effects of the Invention
[0020] According to the present invention, a resin-coated ultra-thin glass plate having high impact resistance, good bending resistance and high transparency can be provided. DETAILED DESCRIPTION
[0021] The present invention will be described in more detail.
[0022] Ultra-thin glass (A)
[0023] The thickness of the ultra-thin glass (A) in the present invention needs to be greater than 10 μm and less than 100 μm. From the perspective of the impact resistance of the resin-coated ultra-thin glass, it needs to be greater than 10 μm, preferably greater than 20 μm, and more preferably greater than 30 μm. From the perspective of the bending resistance of the resin-coated ultra-thin glass, it needs to be less than 100 μm, and more preferably less than 80 μm.
[0024] The ultra-thin glass (A) in the present invention is not particularly limited, and examples thereof include aluminosilicate glass, soda glass, and alkali-free glass. However, from the viewpoint of the bending resistance of the resin-coated ultra-thin glass, tempered glass is preferred.
[0025] The tempered glass mentioned here refers to a glass substrate that has been subjected to a tempering treatment, and preferably has a compressive stress layer on the glass surface.
[0026] As a method for forming a compressive stress layer, it is known that there are physical strengthening methods such as using the expansion and contraction of glass caused by heating and cooling, chemical strengthening methods such as exchanging alkali ions in the glass with other alkali ions with larger ion radius, etc. These methods are all well known, and any method can be selected. In the case of a thin strengthened glass substrate such as the cover glass of a touch panel, it is preferably a glass strengthened by a chemical strengthening method, so-called chemically strengthened glass.
[0027] Among chemically strengthened glasses, aluminum silicate chemically strengthened glass, soda-lime chemically strengthened glass, and the like are more preferable.
[0028] Examples of non-strengthened ultra-thin plate glass (A) include: “AF32 (registered trademark)” eco series (manufactured by Schott), “Corning (registered trademark)”, “Willow (registered trademark)” glass series (manufactured by Corning), “G-Leaf (registered trademark)” series (manufactured by NIPPON ELECTRIC GLASS (Co., Ltd.)), and “SPOOL (registered trademark)” series (manufactured by AGC (Co., Ltd.).
[0029] Examples of chemically strengthened ultra-thin plate glass (A) include: "Xensation (registered trademark)" series (manufactured by Schott), "Corning (registered trademark)", "Gorilla (registered trademark)" glass (Glass) series (manufactured by Corning), "Dinorex (registered trademark)" series (manufactured by Nippon Electric Glass (Co., Ltd.)), and "Dragontrail (registered trademark)" (manufactured by AGC (Co., Ltd.)) series.
[0030] Organic film (B)
[0031] In the present invention, an ultra-thin glass sheet (A) has an organic film (B) formed of a composition containing a thermoplastic resin (D) having a weight average molecular weight of 1,000 to 70,000 on one surface thereof.
[0032] The resin composition suitable as the organic film (B) is described below. The organic film (B) is preferably a buffer film (b). The buffer film (b) is an organic film that mitigates external impact on the resin-coated ultra-thin plate glass to improve impact resistance.
[0033] The film thickness of the organic film (B) is preferably greater than 10 μm and less than 100 μm. From the perspective of further improving the impact resistance of the resin-coated ultra-thin glass of the present invention, it is preferably greater than 10 μm, more preferably greater than 15 μm, and further preferably greater than 30 μm. From the perspective of further improving the bending resistance of the resin-coated ultra-thin glass of the present invention, it is preferably less than 100 μm, more preferably less than 70 μm, and further preferably less than 50 μm.
[0034] Regarding the organic film (B) in the present invention, from the viewpoint of color reproducibility and transparency of the display, it is preferred that the yellowness (yellowness index (YI)) specified in Japanese Industrial Standards (JIS) K7373:2006 for transmitted light from a D65 light source based on the International Commission on Illumination (CIE) standard is |YI|<20, more preferably |YI|<5, and even more preferably |YI|<2.
[0035] Preferably, a hard coating layer is laminated on the surface of the organic film (B) that is not on the ultra-thin glass (A) side. The film thickness of the hard coating layer is preferably greater than 1 μm and less than 20 μm. From the viewpoint of further improving the surface hardness and impact resistance of the resin-coated ultra-thin glass of the present invention, it is preferably greater than 1 μm, and more preferably greater than 5 μm. The surface hardness described here refers to the hardness obtained in the pencil hardness test (load 750 g) based on JIS K5600-5-4 (1999). From the viewpoint of further improving the bending resistance of the resin-coated ultra-thin glass, it is preferably less than 20 μm, and more preferably less than 15 μm.
[0036] The hard coat layer can be formed by a thermosetting resin or a resin with a free radical polymerizable group, but since ultraviolet curing can be performed, it is preferably a resin containing a free radical polymerizable group from the viewpoint of productivity. As the free radical polymerizable group, preferably vinyl, allyl, acrylic, methacrylic, etc. are used. As the resin with the free radical polymerizable group, monomers with free radical polymerizable groups and high molecular polymers with free radical polymerizable groups can be listed. The hard coat layer can use a resin with a free radical polymerizable group alone, or can be mixed with two or more and used simultaneously. Furthermore, in the resin with these free radical polymerizable groups, a third component such as microparticles or ultramicroparticles composed of one or more light free radical initiators, photosensitizers, surfactants, thermosetting resins, metal oxides, solvents or acrylic components can be added for use.
[0037] The resin composition suitable as the organic film (B) in the present invention contains a thermoplastic resin (D) as an essential component and preferably contains a solvent from the viewpoint of coating properties.
[0038] Thermoplastic resin (D)
[0039] The weight average molecular weight of the thermoplastic resin (D) in the present invention needs to be 1000 to 70000. From the perspective of the impact resistance of the resin-coated ultra-thin glass of the present invention, the weight average molecular weight needs to be 1000 or more, more preferably 5000 or more, and even more preferably 10000 or more. On the other hand, from the perspective of the bending resistance of the organic film (B) of the present invention, the weight average molecular weight needs to be 70000 or less, more preferably 35000 or less, and even more preferably 25000 or less. Here, the so-called weight average molecular weight refers to the standard polystyrene conversion value obtained by gel permeation chromatography.
[0040] The glass transition temperature (Tg) of the thermoplastic resin (D) in the present invention is preferably 40°C to 110°C. From the viewpoint of further improving the impact resistance of the resin-coated ultra-thin glass, it is preferably 40°C or higher, more preferably 50°C or higher, and further preferably 60°C or higher. From the viewpoint of further improving the impact resistance of the resin-coated ultra-thin glass, it is preferably 110°C or lower, more preferably 100°C or lower, and further preferably 75°C or lower. Here, the so-called glass transition temperature (Tg) means the glass transition temperature measured by differential scanning calorimetry (DSC).
[0041] As the thermoplastic resin (D) in the present invention, preferably, polyester resin, (meth) acrylate resin, polyester carbamate resin, carbamate resin, silicone resin, cellulose resin, polyolefin resin, epoxy resin, vinyl chloride-vinyl acetate copolymer resin, etc. can be listed. Among these resins, polyester resin and (meth) acrylate resin are preferred from the viewpoint of impact resistance and transparency of the resin-coated ultra-thin plate glass of the present invention. These resins can be used alone or in combination of two or more.
[0042] Examples of the polyester resin include: Vylon (registered trademark) 200 (weight average molecular weight: 17,000, Tg: 67°C), Vylon 220 (weight average molecular weight: 3,000, Tg: 53°C), Vylon 226 (weight average molecular weight: 8,000, Tg: 65°C), Vylon 240 (weight average molecular weight: 15,000, Tg: 60°C), Vylon 241 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 242 (weight average molecular weight: 15,000, Tg: 60°C), Vylon 243 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 244 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 245 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 246 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 247 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 248 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 249 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 240 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 241 (weight average molecular weight: 16,000, Tg: 60°C), Vylon 242 (weight average molecular weight: 16,000, Tg: Vylon 270 (weight average molecular weight 23000, Tg: 67°C), Vylon 290 (weight average molecular weight: 22000, Tg: 72°C), Vylon 660 (weight average molecular weight: 8000, Tg: 55°C), Vylon 802 (weight average molecular weight: 3000, Tg: 60°C), Vylon 882 (weight average molecular weight: 150 00, Tg: 68°C), "Vylon" 885 (weight average molecular weight: 8000, Tg: 79°C), "Vylon" GK-250 (weight average molecular weight: 10000, Tg: 60°C), "Vylon" GK-360 (weight average molecular weight: 16000, Tg: 56°C), "Vylon" GK-880 (weight average molecular weight: 18000, Tg: 84°C), "Vylon" "Vylon" 103 (weight average molecular weight: 23000, Tg: 47°C), "Vylon" 600 (weight average molecular weight: 16000, Tg: 47°C), "Vylon" GK-800 (weight average molecular weight: 27000, Tg: 50°C), "Vylon" GK-810 (weight average molecular weight: 6000, Tg: 46°C) (the above are trade names, manufactured by Toyobo Co., Ltd.), etc. Examples of the (meth)acrylate resin include "Hi-pearl (registered trademark)" M-4006 (weight average molecular weight: 35000, Tg: 105°C), etc. Two or more of these resins may also be contained.
[0043] In the present invention, the organic film (B) preferably contains a thermosetting resin.
[0044] In the present invention, the organic film (B) is formed from a composition containing a thermoplastic resin (D) having a weight average molecular weight of 1,000 to 70,000. From the viewpoint of further improving the surface hardness, the composition containing the thermoplastic resin (D) preferably contains a thermosetting resin.
[0045] As the thermosetting resin, (meth)acrylate compounds, epoxy compounds, melamine compounds, etc. can be cited, and from the viewpoint of stability over time, (meth)acrylate compounds are preferred. As the (meth)acrylate compound, from the viewpoint of both the bending resistance and the surface hardness of the organic film (B), urethane (meth)acrylate compounds are preferred.
[0046] The content of the carbamate (meth) acrylate compound is preferably 5% to 35% by weight in the total solid content of the organic film (B). From the perspective of further improving the surface hardness and impact resistance of the organic film (B), it is preferably 5% by weight or more. From the perspective of further improving the bending resistance and yellowness of the organic film (B), it is preferably 35% by weight or less, more preferably 25% by weight or less, and further preferably 15% by weight or less. Here, the so-called total solid content refers to all components other than the solvent in the organic film (B). The double bond equivalent of the carbamate (meth) acrylate of the present invention is preferably 100g / mol to 600g / mol. From the perspective of further improving the bending resistance of the organic film (B), it is preferably 100g / mol or more. From the perspective of further improving the surface hardness of the resin-coated ultra-thin plate glass, it is preferably 600g / mol or less, more preferably 250g / mol or less, and further preferably 150g / mol or less.
[0047] From the viewpoint of coating properties, the composition containing the thermoplastic resin (D) preferably contains a solvent. Examples of the solvent include ester solvents, ether solvents, acetate solvents, alcohol solvents, ketone solvents, lactone solvents, etc. Two or more of these solvents may also be contained. In addition, solvents such as xylene, ethylbenzene, and solvent naphtha may also be used in combination.
[0048] Examples of the ester solvent include benzyl acetate, ethyl benzoate, γ-butyrolactone, methyl benzoate, diethyl malonate, 2-ethylhexyl acetate, 2-butoxyethyl acetate, 3-methoxy-3-methyl-butyl acetate, diethyl oxalate, ethyl acetoacetate, 3-methoxy-butyl acetate, methyl acetoacetate, ethyl-3-ethoxypropionate, 2-ethylbutyl acetate, isopentyl propionate, propylene glycol monomethyl ether propionate, propylene glycol monoethyl ether acetate, amyl acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, ethyl acetate, butyl acetate, isopentyl acetate, etc. Among these solvents, acetate solvents such as 3-methoxy-3-methyl-butyl acetate and propylene glycol monoethyl ether acetate, and propionate solvents such as propylene glycol monomethyl ether propionate are preferred, and 3-methoxy-butyl acetate and propylene glycol monomethyl ether acetate are more preferred.
[0049] Examples of the ether solvent include propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol tert-butyl ether, diethylene glycol methyl ethyl ether, and dipropylene glycol monomethyl ether.
[0050] Examples of the alcohol solvent include butanol, 3-methyl-2-butanol, and 3-methyl-3-methoxybutanol.
[0051] Examples of the ketone solvent include cyclopentanone and cyclohexanone.
[0052] Examples of the lactone solvent include γ-butyrolactone, γ-valerolactone, and δ-valerolactone.
[0053] The composition containing the thermoplastic resin (D) may contain other additives. Examples of other additives include adhesion improvers, surfactants, polymerization inhibitors, antioxidants, and the like.
[0054] Examples of the adhesion improver include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.
[0055] Examples of the surfactant include: fluorine-based surfactants; silicone-based surfactants; fluorine-containing thermally decomposable surfactants; polyether-modified silicone-based surfactants; polyalkylene oxide-based surfactants; poly(meth)acrylate-based surfactants; anionic surfactants such as ammonium lauryl sulfate and polyoxyethylene alkyl ether triethanolamine sulfate; cationic surfactants such as stearylamine acetate and lauryl trimethylammonium chloride; amphoteric surfactants such as lauryl dimethylamine oxide and lauryl carboxyl methyl hydroxyethyl imidazolium betaine; nonionic surfactants such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, and sorbitan monostearate, etc. Two or more of these surfactants may be contained.
[0056] Among these surfactants, from the viewpoint of suppressing poor coating properties such as dents, reducing surface tension, and suppressing unevenness during coating film drying, preferred are fluorine-based surfactants, silicone-based surfactants, fluorine-containing thermally decomposable surfactants, and polyether-modified siloxane-based surfactants, and more preferred are fluorine-containing thermally decomposable surfactants.
[0057] Examples of commercially available fluorine-based surfactants include: Megafac (registered trademark) F142D, Megafac (registered trademark) F172, Megafac (registered trademark) F173, Megafac (registered trademark) F183, Megafac (registered trademark) F445, Megafac (registered trademark) F470, Megafac (registered trademark) F475, Megafac (registered trademark) F477 (all manufactured by DIC Corporation), NBX-15, and FTX-218 (manufactured by NEOS Corporation). Examples of commercially available silicone surfactants include BYK-333, BYK-301, BYK-331, BYK-345, and BYK-307 (manufactured by BYK-Chemie Japan Co., Ltd.). Examples of commercially available fluorinated thermally decomposable surfactants include Megafac DS-21 (manufactured by DIC Co., Ltd.). Examples of commercially available products of polyether-modified silicone surfactants include: BYK-345, BYK-346, BYK-347, BYK-348, BYK-349 (all manufactured by BYK-Chemie Japan Co., Ltd.), SAG002, SAG005, SAG0503A, and SAG008 (all manufactured by Nissin Chemical Industries, Ltd.).
[0058] Examples of the polymerization inhibitor include hydroquinone-based and catechol-based polymerization inhibitors. Examples of the hydroquinone-based polymerization inhibitor include hydroquinone, tert-butyl hydroquinone, 2,5-bis(1,1,3,3-tetramethylbutyl) hydroquinone, and 2,5-bis(1,1-dimethylbutyl) hydroquinone. Examples of the catechol-based polymerization inhibitor include catechol and tert-butyl catechol.
[0059] Examples of the antioxidant include phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants, etc. Two or more of these antioxidants may be contained.
[0060] Next, the method for producing a composition containing a thermoplastic resin (D) is described.
[0061] The method for producing a composition containing a thermoplastic resin (D) is generally a method in which a thermoplastic resin (D) is heated and stirred in a solvent to prepare a solution of the thermoplastic resin (D), and a predetermined amount of a solvent, a thermosetting resin, a close contact improving agent, a surfactant, a polymerization inhibitor, an antioxidant and other raw materials are mixed into the solution of the thermoplastic resin (D) as required and stirred.
[0062] Organic film (C)
[0063] The ultra-thin glass plate (A) in the present invention has an organic film (C) formed of a composition containing a siloxane resin (E) on the side where the organic film (B) is not formed.
[0064] The following describes a resin composition suitable as the organic film (C) in the present invention. The organic film (C) is preferably a strengthening film (c). The so-called strengthening film (c) is an organic film that prevents cracks in the bending portion of the resin-coated ultra-thin glass and improves the bending resistance of the resin-coated ultra-thin glass.
[0065] The organic film (C) in the present invention is preferably a cured film of a composition containing a siloxane resin (E). The organic film (C) in the present invention is a "cured film" which means that the siloxane resin in the composition is cross-linked by a condensation reaction of a silanol group (thermal cross-linking) or a free radical addition reaction of a free radical polymerizable group (photocross-linking). Furthermore, by performing infrared spectroscopy (IR) analysis on the cured film, it can be determined whether cross-linking is performed based on the presence or absence and size of the peak of the silanol group or the double bond.
[0066] The film thickness of the organic film (C) is preferably 1 μm or more and 20 μm or less. From the perspective of further improving the glass strength of the resin-coated ultra-thin glass, it is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 3 μm or more. From the perspective of further improving the bending resistance of the resin-coated ultra-thin glass, it is preferably 20 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less.
[0067] Preferably, a transparent adhesive layer is laminated on the surface of the organic film (C) that is not on the ultra-thin glass (A) side. Examples of the transparent adhesive layer include: optically clear resin (OCR), optically clear adhesive (OCA) or liquid optically clear adhesives (LOCA). The thickness of the transparent adhesive layer is preferably greater than 10 μm and less than 200 μm. From the viewpoint of further improving the adhesion, it is preferably greater than 10 μm, more preferably greater than 15 μm, and further preferably greater than 20 μm. From the viewpoint of further improving the bending resistance of the resin-coated ultra-thin glass, it is preferably less than 200 μm, more preferably less than 100 μm, and further preferably less than 30 μm.
[0068] The total light transmittance of the transparent adhesive layer is preferably 90% or more. From the perspective of further improving the brightness of the display, it is preferably 90% or more, more preferably 95% or more, and further preferably 98% or more. The total light transmittance referred to here refers to the value measured in accordance with JIS K7361-1.
[0069] The haze value of the transparent adhesive layer is preferably 10% or less. From the viewpoint of further improving the transparency of the display, it is preferably 10% or less, more preferably 5% or less, and further preferably 3% or less. The haze value mentioned here refers to the value measured according to JIS K7136.
[0070] The storage elastic modulus of the transparent adhesive layer at 25°C is preferably 0.05 MPa or more and 1.5 MPa or less. From the perspective of further improving the impact resistance of the resin-coated ultra-thin plate glass, it is preferably 0.05 MPa or more, more preferably 0.10 MPa or more, and further preferably 0.15 MPa or more. From the perspective of further improving the adhesive force, it is preferably 1.5 MPa or less, more preferably 1.0 MPa or less, and further preferably 0.5 MPa or less.
[0071] As the resin constituting the transparent adhesive layer, there can be cited: (meth) acrylic resin, silicone resin, urethane resin, etc., but from the perspective of transparency or stability in the visible light region, (meth) acrylic resin is preferred. The transparent adhesive layer can use a single resin, or mix two or more resins to use simultaneously. Furthermore, one or more of the third components such as monomers, crosslinking agents, solvents, silane coupling agents, antistatic agents, adhesion imparting agents, antioxidants, ultraviolet absorbers, and leveling agents can be added to these resins for use.
[0072] Silicone resin (E)
[0073] The resin composition suitable as the organic film (C) in the present invention contains the siloxane resin (E) as an essential component and preferably contains a solvent from the viewpoint of coating properties.
[0074] The siloxane resin (E) in the present invention refers to a polymer containing a repeating unit having a siloxane skeleton, and is preferably a hydrolysis condensate of an organic silane compound. When the siloxane resin (E) has an oxetane group, it is classified as a "siloxane compound having an oxetane group" described below.
[0075] From the viewpoint of improving coating properties, the weight average molecular weight of the siloxane resin (E) in the present invention is preferably 2,000 to 7,000.
[0076] The content of phenyl in the siloxane resin (E) in the present invention is preferably 5 mol% to 60 mol% relative to Si atoms. From the perspective of relaxing film stress and further improving the bending resistance of the resin-coated ultra-thin glass, the content of phenyl in the siloxane resin (E) is preferably 5 mol% or more relative to Si atoms. From the perspective of increasing the crosslinking degree of the organic film (C) and further improving the bending resistance of the resin-coated ultra-thin glass, it is preferably 60 mol% or less.
[0077] The siloxane resin (E) in the present invention preferably has a free radical polymerizable group. By having a photo-free radical polymerization initiator and a free radical polymerizable group described later, the free radical polymerization reaction caused by free radicals generated by light irradiation can be used to increase the crosslinking degree of the organic film (C) in the present invention, and further improve the bending resistance of the resin-coated ultra-thin plate glass.
[0078] As free radical polymerizable groups, for example, vinyl, α-methylvinyl, allyl, styryl, (meth)acryloyl, etc. can be cited. From the viewpoint of further improving the degree of crosslinking of the organic film (C) in the present invention, (meth)acryloyl is preferred. As a siloxane resin having a free radical polymerizable group, a hydrolysis condensate of an organic silane compound having a free radical polymerizable group is preferred. It can also be a hydrolysis condensate of an organic silane compound having a free radical polymerizable group and other organic silane compounds. As an organic silane compound having a free radical polymerizable group, for example, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriacetoxysilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, allylmethyldimethoxysilane, allylmethyldiethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane Alkane, p-phenylenedimethyl dimethoxysilane, p-phenylenedimethyl diethoxysilane, 3-acryloxypropyl trimethoxysilane, 3-acryloxypropyl triethoxysilane, 3-acryloxypropyl methyl dimethoxysilane, 3-acryloxypropyl methyl diethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl triethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, etc. It is also possible to use two or more of these compounds. Among these compounds, with respect to further improving the crosslinking degree of organic film (C), further improving the viewpoint of the bending resistance of resin-coated ultra-thin plate glass, preferably 3-acryloxypropyl trimethoxysilane, 3-acryloxypropyl triethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-methacryloxypropyl triethoxysilane.
[0079] Examples of other organosilane compounds include methyltrimethoxysilane, methyltriethoxysilane, methyltriproxylsilane, methyltriisopropoxysilane, methyltributoxysilane, methyltriproxylsilane, dimethyldimethoxysilane, dimethyldiethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, diethyldimethoxysilane, n-propyltrimethoxysilane, isopropyltrimethoxysilane, diisopropyldimethoxysilane, n-butyltrimethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, diisobutyldimethoxysilane, n-hexyltrimethoxysilane, and n-hexyltriethoxysilane. silane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, trifluoromethyltrimethoxysilane, trifluoromethyltriethoxysilane, trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane propyl triethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, N-(1,3-dimethylbutylene)-3-aminopropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropylmethyldimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-( 3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, tris(trimethoxysilylpropyl)isocyanurate, bis(3-(triethoxysilyl)propyl)disulfide, bis(3-(triethoxysilyl)propyl)tetrasulfide, 3-trimethoxysilylpropylsuccinic anhydride, 3-triethoxysilylpropylsuccinic anhydride, etc. Two or more of these compounds may be used.
[0080] The siloxane resin (E) in the present invention can be obtained by hydrolyzing and condensing an organosilane compound, for example, by hydrolyzing an organosilane compound and then subjecting the resulting silanol compound to a condensation reaction in the presence of a solvent or in the absence of a solvent.
[0081] The various conditions of the hydrolysis reaction can be appropriately set in consideration of the reaction scale, the size and shape of the reaction vessel, etc. For example, it is preferred that the reaction is carried out at room temperature to 110° C. for 1 minute to 180 minutes after adding an acid catalyst and water to the organosilane compound in a solvent. By carrying out the hydrolysis reaction under such conditions, a rapid reaction can be suppressed. The reaction temperature is more preferably 30° C. to 105° C.
[0082] The hydrolysis reaction is preferably carried out in the presence of an acid catalyst. As the acid catalyst, an acidic aqueous solution containing formic acid, acetic acid, or phosphoric acid is preferred. The amount of the acid catalyst added is preferably 0.1 to 5 parts by weight relative to 100 parts by weight of all the organosilane compounds used during the hydrolysis reaction. By setting the amount of the acid catalyst to the above range, the hydrolysis reaction can be carried out more efficiently.
[0083] After obtaining the silanol compound by the hydrolysis reaction of the organosilane compound, the reaction solution is preferably heated at 50° C. or higher and below the boiling point of the solvent for 1 to 100 hours to carry out the condensation reaction. Further heating or addition of an alkali catalyst may be performed to increase the polymerization degree of the polysiloxane. Examples of the solvent used in the hydrolysis reaction of the organosilane compound and the condensation reaction of the silanol compound include: alcohols such as methanol, ethanol, propanol, isopropanol, butanol, isobutanol, tert-butanol, pentanol, 4-methyl-2-pentanol, 3-methyl-2-butanol, 3-methoxy-1-butanol, 3-methyl-3-methoxy-1-butanol, 1-tert-butoxy-2-propanol, and diacetone alcohol; glycols such as ethylene glycol and propylene glycol; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, Ethers such as diethyl ether; ketones such as methyl ethyl ketone, acetylacetone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclopentanone, 2-heptanone; amides such as dimethylformamide and dimethylacetamide; acetates such as ethyl acetate, propyl acetate, butyl acetate, isobutyl acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, methyl lactate, ethyl lactate, butyl lactate; aromatic or aliphatic hydrocarbons such as toluene, xylene, hexane, cyclohexane, γ-butyrolactone, N-methyl-2-pyrrolidone, dimethyl sulfoxide, etc. From the viewpoint of further improving the transmittance and crack resistance of the organic film (C), diacetone alcohol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, propylene glycol mono-tert-butyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, γ-butyrolactone, etc. can be preferably used.
[0084] In the case where a solvent is generated by a hydrolysis reaction, the hydrolysis may be performed without a solvent. It is also preferred that a solvent is further added after the reaction is completed to adjust the concentration to be appropriate as a composition. In addition, it is also possible to distill an appropriate amount of generated alcohol etc. under heating and / or reduced pressure after hydrolysis and remove it according to the purpose, and then add a suitable solvent.
[0085] The amount of the solvent used in the hydrolysis reaction is preferably 80 to 500 parts by weight based on 100 parts by weight of the total organosilane compound. By setting the amount of the solvent to be within the above range, the hydrolysis reaction can be performed more efficiently.
[0086] In addition, the water used in the hydrolysis reaction is preferably ion-exchanged water, and the amount of water is preferably 1.0 mol to 4.0 mol per 1 mol of silicon atoms.
[0087] From the viewpoint of further improving the bending resistance and transparency of the resin-coated ultra-thin glass, the content of the siloxane resin (E) in the composition containing the siloxane resin (E) is preferably 15% by weight or more, more preferably 25% by weight or more of the total solid content. On the other hand, from the viewpoint of further improving the bending property of the organic film (C), the content of the siloxane resin is preferably 90% by weight or less, more preferably 80% by weight or less of the total solid content.
[0088] From the viewpoint of coating properties, the composition containing the siloxane resin (E) preferably contains a solvent. By containing a solvent, each component can be uniformly dissolved. As a solvent, for example, aliphatic hydrocarbons, carboxylates, ketones, ethers, alcohols, etc. can be listed. Two or more of these solvents may also be contained. From the viewpoint of uniformly dissolving each component and improving the transparency of the obtained coating film, a compound having an alcoholic hydroxyl group or a cyclic compound having a carbonyl group is preferred.
[0089] Examples of the compound having an alcoholic hydroxyl group include acetone alcohol, 3-hydroxy-3-methyl-2-butanone, 4-hydroxy-3-methyl-2-butanone, 5-hydroxy-2-pentanone, 4-hydroxy-4-methyl-2-pentanone (diacetone alcohol), ethyl lactate, butyl lactate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol mono-n-butyl ether, propylene glycol mono-tert-butyl ether, 3-methoxy-1-butanol, and 3-methyl-3-methoxy-1-butanol. Among these compounds, diacetone alcohol and 3-methyl-3-methoxy-1-butanol are preferred from the viewpoint of storage stability.
[0090] Specific examples of the cyclic compound having a carbonyl group include γ-butyrolactone, γ-valerolactone, δ-valerolactone, propylene carbonate, N-methylpyrrolidone, cyclohexanone, cycloheptanone, etc. Among these compounds, γ-butyrolactone can be used particularly preferably.
[0091] Examples of the aliphatic hydrocarbon include xylene, ethylbenzene, and solvent naphtha.
[0092] Examples of the carboxylic acid ester include benzyl acetate, ethyl benzoate, γ-butyrolactone, methyl benzoate, diethyl malonate, 2-ethylhexyl acetate, 2-butoxyethyl acetate, 3-methoxy-3-methyl-butyl acetate, diethyl oxalate, ethyl acetoacetate, cyclohexyl acetate, 3-methoxy-butyl acetate, methyl acetoacetate, ethyl-3-ethoxypropionate, 2-ethylbutyl acetate, isopentyl propionate, propylene glycol monomethyl ether propionate, propylene glycol monoethyl ether acetate, ethyl acetate, butyl acetate, isopentyl acetate, amyl acetate, and propylene glycol monomethyl ether acetate.
[0093] Examples of the ketone include cyclopentanone and cyclohexanone.
[0094] Examples of the ether include aliphatic ethers such as propylene glycol derivatives such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol tert-butyl ether, and dipropylene glycol monomethyl ether.
[0095] From the viewpoint of appropriately adjusting the volatility and drying characteristics when applying the composition containing the siloxane resin (E) to the ultra-thin plate glass (A) and improving the coating properties, it is preferred to contain a solvent having a boiling point of 150° C. to 250° C. at atmospheric pressure and a solvent having a boiling point of less than 150° C. at atmospheric pressure. The boiling point of the solvent having a boiling point of 150° C. to 250° C. at atmospheric pressure is more preferably 150° C. to 200° C. or less.
[0096] Examples of the solvent having a boiling point of 150° C. to 250° C. under atmospheric pressure include 4-hydroxy-4-methyl-2-pentanone (diacetone alcohol), ethyl lactate, butyl lactate, propylene glycol mono-tert-butyl ether, 3-methoxy-1-butanol, 3-methyl-3-methoxy-1-butanol, benzyl acetate, ethyl benzoate, methyl benzoate, diethyl malonate, 2-ethylhexyl acetate, 2-butoxyethyl acetate, 3-methoxy-3-methyl-butyl acetate, diethyl oxalate, ethyl acetoacetate, cyclohexyl acetate, 3-methoxy-butyl acetate, methyl acetoacetate, ethyl-3-ethoxypropionate, isopentyl propionate, propylene glycol monomethyl ether propionate, γ-butyrolactone, γ-valerolactone, δ-valerolactone, propylene carbonate, N-methylpyrrolidone, cyclohexanone, and cycloheptanone. Among these solvents, 4-hydroxy-4-methyl-2-pentanone (diacetone alcohol), 3-methyl-3-methoxy-1-butanol, 3-methoxy-3-methyl-butyl acetate, 3-methoxy-butyl acetate, and γ-butyrolactone can be particularly preferably used.
[0097] Examples of the solvent having a boiling point of less than 150° C. under atmospheric pressure include methyl acetate, ethyl acetate, isopropyl acetate, n-propyl acetate, butyl acetate, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol ethyl ether, ethylene glycol methyl ether, butanol, isobutyl alcohol, n-propanol, and ethyl acetate. Among these solvents, propylene glycol monomethyl ether acetate and propylene glycol monomethyl ether are particularly preferably used.
[0098] The composition containing siloxane resin (E) preferably contains silica particles, and may also contain other components. The composition containing siloxane resin (E) can take into account the bending resistance and transparency of resin-coated ultra-thin plate glass at a high level by containing silica particles. The composition containing siloxane resin is preferably that the content of silica particles is more than 10 weight % and less than 40 weight % in the total solids. Here, the so-called total solids refer to all components other than the solvent in the composition containing siloxane resin (E). By setting the content of silica particles to more than 10 weight % in the total solids, crosslinking can be promoted by the silanol condensation reaction of siloxane resin (E) and silica particles, the crosslinking degree of the organic film (C) in the present invention is improved, and the bending resistance of resin-coated ultra-thin plate glass is further improved. In addition, the refractive index difference between ultra-thin plate glass (A) and organic film (C) can be reduced, and the unevenness caused by the film thickness deviation of organic film (C) can be alleviated. By setting the content of the silica particles to 40% by weight or less in the total solid content, an organic film (C) having excellent bending resistance and adhesion can be obtained.
[0099] From the viewpoint of further improving the transparency of the organic film (C) in the present invention, the average particle size of the silica particles is preferably 1 nm to 200 nm, more preferably 1 nm to 70 nm. Here, the average particle size of the silica particles can be obtained by a dynamic light scattering method. Specifically, for a dispersion having a silica particle concentration of 10 wt % to 30 wt %, a semiconductor laser is used to irradiate light having a wavelength of 780 nm, and after measuring the scattered light, a frequency analysis is performed using a fast Fourier transform (FFT)-heterodyne method, thereby the average particle size can be obtained.
[0100] Examples of silica particles include Sicastar (manufactured by Corefront Co., Ltd.), Reolosil (registered trademark) (manufactured by Tokuyama Co., Ltd.), etc. These particles may be crushed or dispersed using a disperser such as a bead mill. Examples of the dispersion of silica particles include IPA-ST, MIBK-ST, IPA-ST-L, IPA-ST-ZL, PGM-ST, PMA-ST (all manufactured by Nissan Chemical Industries, Ltd.), "Oscal (registered trademark)" 101, "Oscal (registered trademark)" 105, "Oscal (registered trademark)" 106, "Cataloid (registered trademark)"-S (all manufactured by Nissan Catalyst Chemicals, Ltd.), "Quartron (registered trademark)" PL-1-IPA, PL-1-Tol, PL-2L-PGME, PL-2L-MEK, PL-2L, GP-2L (all manufactured by Fuso Chemical Industries, Ltd.), etc. Two or more of these compounds may be contained.
[0101] The composition containing the siloxane resin (E) preferably contains a photoradical polymerization initiator. By combining it with a siloxane resin (E) having a radical polymerizable group, the crosslinking degree of the organic film (C) in the present invention can be increased by photoradical polymerization reaction, and the bending resistance of the resin-coated ultra-thin glass can be further improved.
[0102] In the above case, from the viewpoint of fully carrying out the reaction of the free radical polymerizable group and further improving the bending resistance of the resin-coated ultra-thin plate glass, the content of the photo-free radical polymerization initiator in the composition containing the siloxane resin (E) is preferably 0.5% by weight or more, more preferably 1% by weight or more in the total solid content. On the other hand, from the viewpoint of further improving the transparency of the organic film (C) in the present invention, the content of the photo-free radical polymerization initiator is preferably 20% by weight or less, more preferably 10% by weight or less in the total solid content.
[0103] Examples of the photoradical polymerization initiator include: alkyl phenone photoradical polymerization initiators such as α-aminoalkyl phenone photoradical polymerization initiators or α-hydroxyalkyl phenone photoradical polymerization initiators; acylphosphine oxide photoradical polymerization initiators; oxime ester photoradical polymerization initiators; benzophenone photoradical polymerization initiators; thioxanthone photoradical polymerization initiators; imidazole photoradical polymerization initiators; benzothiazole photoradical polymerization initiators; benzoxazole photoradical polymerization initiators; carbazole photoradical polymerization initiators; triazine photoradical polymerization initiators; benzoate photoradical polymerization initiators; phosphorus photoradical polymerization initiators; inorganic photoradical polymerization initiators such as titanates, etc. Two or more of these compounds may be contained.
[0104] Among these compounds, from the viewpoint of increasing the degree of crosslinking of the organic film (C) in the present invention and further increasing the bending resistance of the resin-coated ultra-thin glass, preferred are α-aminophenylalkyl ketone-based photoradical polymerization initiators, acylphosphine oxide-based photoradical polymerization initiators, oxime ester-based photoradical polymerization initiators, dibenzophenone-based photoradical polymerization initiators having an amino group, and benzoate-based photoradical polymerization initiators having an amino group.
[0105] Examples of the α-amino alkylphenone-based photoradical polymerization initiator include 2-methyl-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholino-4-yl-phenyl)-butan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1. Examples of the acylphosphine oxide-based photoradical polymerization initiator include 2,4,6-trimethylbenzoylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-(2,4,4-trimethylpentyl)-phosphine oxide. Examples of the oxime ester photoradical polymerization initiator include 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)], 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1,3-diphenylacetone-2-(o-ethoxycarbonyl)oxime, ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetyloxime), etc. Examples of the benzophenone photoradical polymerization initiator having an amino group include 4,4-bis(dimethylamino)benzophenone, 4,4-bis(diethylamino)benzophenone, etc. Examples of the benzoate-based photoradical polymerization initiator having an amino group include ethyl p-dimethylaminobenzoate, 2-ethylhexyl-p-dimethylaminobenzoate, and ethyl p-diethylaminobenzoate.
[0106] The composition containing the siloxane resin (E) preferably further contains a compound having two or more free radical polymerizable groups. By containing a compound having two or more free radical polymerizable groups, the degree of crosslinking of the organic film (C) in the present invention can be increased and the bending resistance of the resin-coated ultra-thin plate glass can be further improved by utilizing a free radical polymerization reaction with the free radical polymerizable groups contained in the siloxane resin (E).
[0107] Examples of the radical polymerizable group include the groups exemplified as the radical polymerizable group possessed by the siloxane resin.
[0108] As a compound having two or more free radical polymerizable groups, a polyfunctional (meth)acrylate is preferably used. The so-called polyfunctional (meth)acrylate refers to a compound having two or more (meth)acrylate groups, for example, 2,2-[9H-fluorene-9,9-diylbis(1,4-phenylene)bisoxy]diethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, glycerol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate. Compounds having two (meth)acrylate groups such as 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, etc.; acrylate of tri(2-hydroxyethyl)isocyanuric acid, glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol nona(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, pentaerythritol undeca(meth)acrylate, pentaerythritol dodeca(meth)acrylate, etc. Two or more of these compounds may be contained.
[0109] From the viewpoint of increasing the degree of crosslinking of the organic film (C) and further increasing the bending resistance of the resin-coated ultra-thin glass, the content of the compound having two or more free radical polymerizable groups in the composition containing the siloxane resin (E) is preferably 5% by weight or more, more preferably 10% by weight or more in the total solid content. On the other hand, from the viewpoint of further increasing the bending property of the organic film (C), the content of the compound having two or more free radical polymerizable groups is preferably 50% by weight or less, more preferably 30% by weight or less in the total solid content.
[0110] The composition containing the siloxane resin (E) may also contain a siloxane compound having an oxetane group. By containing a siloxane compound having an oxetane group, the stress of the organic film (C) is relaxed by the ring-opening reaction of the oxetane ring, and the adhesion between the ultra-thin plate glass (A) and the organic film (C) can be improved.
[0111] Examples of the siloxane compound having an oxetanyl group include compounds represented by the following general formula (1).
[0112] [Chemistry 1]
[0113]
[0114] In the general formula (1), R 1 ~R 4 represents a hydrogen atom, an alkyl group, a cycloalkyl group or a group represented by the following general formula (2). 1 ~R 4 At least one of them is a group represented by the following general formula (2). w represents an integer of 1 to 10. From the viewpoint of reactivity, the number of carbon atoms in the alkyl group is preferably 1 to 6, and the number of carbon atoms in the cycloalkyl group is preferably 3 to 6.
[0115] [Chemistry 2]
[0116]
[0117] In the general formula (2), R 5 ~R 9 represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 4 carbon atoms, a phenyl group, or a perfluoroalkyl group having 1 to 4 carbon atoms. p represents an integer of 1 to 6.
[0118] The siloxane compound represented by the general formula (1) can be obtained by hydrolyzing an alkoxysilane compound having an oxetane group together with an alkoxysilane compound not having an oxetane group, if necessary.
[0119] Examples of the alkoxysilane compound having an oxetane group include (oxetane-3-yl)methyltrimethoxysilane, (oxetane-3-yl)methyltriethoxysilane, (oxetane-3-yl)methyltri-n-propyloxysilane, (oxetane-3-yl)methyltri-isopropyloxysilane, (oxetane-3-yl)methyltriacetoxysilane, (oxetane-3-yl)methylmethyldimethoxysilane, (oxetane-3-yl)methylmethyldiethoxysilane, (oxetane-3-yl)methylmethyldi-n-propyloxysilane, (oxetane-3-yl)methylmethyldi-isopropyloxysilane, (oxetane-3-yl)methylmethyldiacetoxysilane silane, (oxetane-3-yl)methylethyldimethoxysilane, (oxetane-3-yl)methylethyldiethoxysilane, (oxetane-3-yl)methylethyldi-n-propyloxysilane, (oxetane-3-yl)methylethyldi-isopropyloxysilane, (oxetane-3-yl)methylethyldiacetoxysilane, (oxetane-3-yl)methylphenyldimethoxysilane, (oxetane-3-yl)methylphenyldiethoxysilane, (oxetane-3-yl)methylphenyldi-n-propyloxysilane, (oxetane-3-yl)methylphenyldi-isopropyloxysilane, (oxetane-3-yl)methylphenyldiacetoxysilane, di(oxetane-3-yl)methylphenyl bis(oxetane-3-yl)methyldimethoxysilane, bis(oxetane-3-yl)methyldiethoxysilane, bis(oxetane-3-yl)methyldi-n-propyloxysilane, bis(oxetane-3-yl)methyldi-isopropyloxysilane, bis(oxetane-3-yl)methyldiacetoxysilane, bis(oxetane-3-yl)methylmethylmethoxysilane, bis(oxetane-3-yl)methylmethylethoxysilane, bis(oxetane-3-yl)methylmethyl-n-propyloxysilane, bis(oxetane-3-yl)methylmethyl-isopropyloxysilane, bis(oxetane-3-yl)methylmethylacetoxysilane, bis(oxetane-3-yl)methylethylmethoxysilane, bis(oxetane-3-yl)methyl 1-Butane-3-yl)methylethylethoxysilane, bis(oxetan-3-yl)methylethyl-n-propyloxysilane, bis(oxetan-3-yl)methylethyl-isopropyloxysilane, bis(oxetan-3-yl)methylethylacetoxysilane, bis(oxetan-3-yl)methylphenylmethoxysilane, bis(oxetan-3-yl)methylphenylethoxysilane, bis(oxetan-3-yl)methylphenyl-n-propyloxysilane, bis(oxetan-3-yl)methylphenyl-isopropyloxysilane, bis(oxetan-3-yl)methylphenylacetoxysilane, tris(oxetan-3-yl)methylmethoxysilane, tris(oxetan-3-yl)methylethoxysilane,Tri(oxetane-3-yl)methyl-n-propyloxysilane, tri(oxetane-3-yl)methyl-isopropyloxysilane, tri(oxetane-3-yl)methylacetoxysilane, etc. Two or more of these compounds may be used.
[0120] Examples of the alkoxysilane compound not having an oxetane group include tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltriisopropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, cyclohexyltrimethoxysilane, cyclohexyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldiethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, trimethylsilanol, triethylsilanol, tripropylsilanol, tributylsilanol, Triphenylsilanol, trimethylmethoxysilane, trimethylethoxysilane, triethylmethoxysilane, triethylethoxysilane, tripropylmethoxysilane, tripropylethoxysilane, trimethylsilyl acetate, trimethylsilylbenzoate, triethylsilyl acetate, triethylsilylbenzoate, benzyldimethylmethoxysilane, benzyldimethylethoxysilane, diphenylmethoxymethylsilane, diphenylethoxymethylsilane, acetyltriphenylsilane, ethoxytriphenylsilane, hexamethyldisiloxane, hexaethyldimethyldisiloxane, hexapropyldisiloxane, 1,3-dibutyl-1,1,3,3-tetramethyldisiloxane, 1,3-diphenyl-1,1,3,3-tetramethyldisiloxane, 1,3-dimethyl-1,1,3,3-tetraphenyldisiloxane, etc. Two or more of these compounds may be used.
[0121] Examples of the siloxane compound having an oxetane group include: "Aron Oxetane (registered trademark)" OXT-191 (trade name, manufactured by Toagosei Co., Ltd.) (R in the general formula (1) is 1 ~R 4 is (3-ethyl-3-oxetanyl)methyl, w is 5 on average), or a compound represented by the following general formula (3) or general formula (6), etc. Two or more of these compounds may be contained.
[0122] [Chemistry 3]
[0123]
[0124] In the general formula (3), R 10 and R 12R represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 6 carbon atoms, a fluoroalkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 18 carbon atoms, a furyl group or a thienyl group. 11 represents a group represented by the following general formula (4). d represents an integer of 0 to 3. Examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, etc. Examples of the fluoroalkyl group having 1 to 6 carbon atoms include trifluoromethyl, perfluoroethyl, perfluoropropyl, etc. Examples of the aryl group having 6 to 18 carbon atoms include phenyl, naphthyl, etc.
[0125] [Chemistry 4]
[0126]
[0127] In the general formula (4), R 13 , R 15 , R 16 and R 18 represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 18 carbon atoms, and R 14 and R 17 represents an alkyl group having 1 to 4 carbon atoms, an aryl group having 6 to 18 carbon atoms, or a group represented by the following general formula (5). u represents an integer from 0 to 200. When u is 2 or more, a plurality of R 14 and R 17 Can be the same or different.
[0128] [Chemistry 5]
[0129]
[0130] In the general formula (5), R 19 ~R 23 represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 18 carbon atoms. Z represents an integer of 0 to 100. When Z is 2 or more, a plurality of R 19 and R 23 Can be the same or different.
[0131] [Chemistry 6]
[0132]
[0133] In the general formula (6), R 24 represents a hydrogen atom, a fluorine atom, an alkyl group having 1 to 6 carbon atoms, a fluoroalkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 18 carbon atoms, a furyl group or a thienyl group, and R 25 represents a trivalent to decavalent organic group. For example, a linear, branched or cage-like polysiloxane-containing group represented by any of the following general formulae (7) to (9) can be cited. In general formula (6), j represents an organic group equal to R 25 An integer from 3 to 10 of the valence of .
[0134] [Chemistry 7]
[0135]
[0136] Examples of the cage-like siloxane compound having an oxetanyl group represented by the general formula (9) include silsesquioxane derivatives OX-SQ TX-100 and OX-SQ SI-20 (these are trade names, manufactured by Toagosei Co., Ltd.).
[0137] Among these compounds, compounds having a plurality of oxetane groups are preferred. Having a plurality of oxetane groups can improve the stress relaxation effect of the organic film (C) caused by the ring-opening reaction of the oxetane ring, and can further improve the adhesion to the glass substrate.
[0138] From the viewpoint of further relaxing the stress of the organic film (C) and further improving the adhesion, the content of the siloxane compound having an oxetane group in the composition containing the siloxane resin (E) is preferably 0.1% by weight or more, more preferably 0.5% by weight or more in the total solid content. On the other hand, from the viewpoint of increasing the stress of the organic film (C) and further improving the bending resistance of the resin-coated ultra-thin plate glass, the content of the siloxane compound having an oxetane group is preferably 10% by weight or less, more preferably 6% by weight or less in the total solid content.
[0139] The composition containing the siloxane resin (E) may also contain a metal chelate compound represented by the following general formula (10). Since the metal chelate compound acts as a catalyst for the silanol condensation reaction of the siloxane resin (E), the crosslinking degree of the organic film (C) becomes higher, which can further improve the bending resistance of the resin-coated ultra-thin glass.
[0140] [Chemistry 8]
[0141]
[0142] In the general formula (10), M represents a metal atom, R 26 represents hydrogen, alkyl, aryl or alkenyl, R 27 and R 28 Each independently represents hydrogen, an alkyl group, an aryl group, an alkenyl group or an alkoxy group. The alkyl group, the aryl group, the alkenyl group or the alkoxy group may be substituted by a substituent. e represents the atomic valence of the metal atom M, and f represents an integer from 0 to e. From the viewpoint of reactivity, ef is preferably 0.
[0143] As the metal atom M, from the viewpoint of transparency of the organic film (C), titanium, zirconium, aluminum, zinc, cobalt, molybdenum, lanthanum, barium, strontium, magnesium, and calcium are preferred, and zirconium and aluminum are more preferred.
[0144] As R26 , for example, hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-octadecyl, phenyl, vinyl, allyl, oleyl, etc. can be mentioned.
[0145] As R 27 and R 28 , for example, hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, phenyl, vinyl, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-octadecyl, benzyloxy, etc.
[0146] Examples of zirconium chelate compounds in which the metal atom M is zirconium include tetra-n-propoxy zirconium, tetra-n-butoxy zirconium, tetra-sec-butoxy zirconium, tetraphenoxy zirconium, zirconium tetraacetylacetonate, zirconium tetra(2,2,6,6-tetramethyl-3,5-heptanedione), zirconium tetramethyl acetoacetate, zirconium tetraethyl acetoacetate, zirconium tetramethyl malonate, zirconium tetraethyl malonate, zirconium tetrabenzoyl acetate, zirconium tetra-dibenzoyl formate, mono-n-butoxy acetylacetonate di- (Ethyl acetoacetate) zirconium, mono-n-butoxyethyl acetoacetate bis(acetylacetonate) zirconium, mono-n-butoxytris(acetylacetonate) zirconium, mono-n-butoxytris(acetylacetonate) zirconium, di-n-butoxybis(ethyl acetoacetate) zirconium, di-n-butoxybis(acetylacetonate) zirconium, di-n-butoxybis(acetylacetonate) zirconium, di-n-butoxybis(ethylmalonate) zirconium, di-n-butoxybis(benzoylpyruvate) zirconium, di-n-butoxybis(dibenzoylformate) zirconium, and the like.
[0147] Examples of aluminum chelate compounds in which the metal atom M is aluminum include triisopropoxyaluminum, tri-n-propoxyaluminum, tri-sec-butoxyaluminum, tri-n-butoxyaluminum, triphenoxyaluminum, aluminum triacetylacetonate, tris(2,2,6,6-tetramethyl-3,5-heptanedione)aluminum, aluminum triacetylacetoacetate, aluminum trimethylacetoacetate, aluminum trimethylmalonate, aluminum triethylmalonate, aluminum ethylacetate di(isopropoxy)acetate, aluminum (acetylacetonate) di(isopropoxy), aluminum methyl acetoacetate di(isopropoxy), aluminum octadecyl acetoacetate di(isopropionate), aluminum monoacetylacetonate bis(ethyl acetoacetate), and the like.
[0148] Among these compounds, tetra-n-propoxy zirconium, tetra-n-butoxy zirconium, tetraphenoxy zirconium, zirconium tetraacetylacetonate, zirconium tetra(2,2,6,6-tetramethyl-3,5-heptanedione), zirconium tetramethylmalonate, zirconium tetraethylmalonate, zirconium tetraethyl acetoacetate, zirconium di-n-butoxybis(ethyl acetoacetate), zirconium mono-n-butoxy acetylacetonate bis(ethyl acetoacetate), aluminum triacetylacetonate, aluminum tri(2,2,6,6-tetramethyl-3,5-heptanedione), aluminum triacetylacetate, aluminum methyl triacetylacetate, aluminum trimethylmalonate, aluminum triethylmalonate, aluminum ethyl acetoacetate di(isopropoxy)acetate, aluminum (acetylacetonate) di(isopropoxy), aluminum methyl acetoacetate di(isopropoxy), aluminum octadecyl acetoacetate di(isopropoxy), and aluminum monoacetylacetonate bis(ethyl acetoacetate).
[0149] From the viewpoint of further improving the crosslinking degree of the organic film (C) and further improving the bending resistance of the resin-coated ultra-thin plate glass, the content of the metal chelate compound in the composition containing the siloxane resin (E) is preferably 0.1% by weight or more, more preferably 0.5% by weight or more in the total solids. On the other hand, from the viewpoint of the temporal stability of the composition containing the siloxane resin (E), the content of the metal chelate compound is preferably 10% by weight or less, more preferably 7% by weight or less in the total solids.
[0150] The composition containing the siloxane resin (E) may contain an adhesion improver. By containing an adhesion improver, the adhesion between the organic film (C) and the ultra-thin plate glass (A) can be further improved.
[0151] Examples of the adhesion improver include silane coupling agents having functional groups such as vinyl, epoxy, styryl, (meth)acryloyloxy, and amino groups. Specifically, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl triethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, 3-glycidyloxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, p-styryl trimethoxysilane, 3-methacryloyloxypropyl trimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane. Silane, 3-acryloxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, 3-mercaptopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-isocyanatepropyltriethoxysilane, etc.
[0152] From the viewpoint of further improving the adhesion between the organic film (C) and the ultra-thin glass (A), the content of the adhesion improver in the composition containing the siloxane resin (E) is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, in the total solid content. On the other hand, from the viewpoint of the temporal stability of the composition containing the siloxane resin (E), it is preferably 10% by weight or less, more preferably 5% by weight or less, in the total solid content.
[0153] The composition containing the siloxane resin (E) may also contain various crosslinking agents to promote or facilitate crosslinking. Examples of the crosslinking agent include nitrogen-containing organic substances, silicone resin crosslinking agents, isocyanate compounds or polymers thereof, methylolated melamine derivatives, methylolated urea derivatives, and the like. Two or more of these crosslinking agents may also be contained. Among them, methylolated melamine derivatives and methylolated urea derivatives may be preferably used from the viewpoint of crosslinking properties and stability over time.
[0154] Since the curing of the siloxane resin (E) is accelerated by an acid, the composition containing the siloxane resin (E) may contain a curing catalyst such as a thermal acid generator or a photoacid generator. Examples of the thermal acid generator include SI-60, SI-80, SI-100, SI-110, SI-145, SI-150, SI-60L, SI-80L, SI-100L, SI-110L, SI-145L, SI-150L, SI-160L, and SI-180L (all manufactured by Sanshin Chemical Industry Co., Ltd.), 4-hydroxyphenyldimethylsulfonium trifluoromethanesulfonate, benzyl-4-hydroxyphenylmethylsulfonium trifluoromethanesulfonate, 2-methylbenzyl-4-hydroxyphenylmethylsulfonium trifluoromethanesulfonate, 4-acetoxyphenyldimethylsulfonium trifluoromethanesulfonate, 4-acetoxyphenylbenzylmethylsulfonium trifluoromethanesulfonate, 4-methoxycarbonyloxyphenyldimethylsulfonium trifluoromethanesulfonate, and benzyl-4-methoxycarbonyloxyphenylmethylsulfonium trifluoromethanesulfonate.
[0155] Examples of the photoacid generator include SI-100, SI-101, SI-105, SI-106, SI-109, PI-105, PI-106, PI-109, NAI-100, NAI-1002, NAI-1003, NAI-1004, NAI-101, NAI-105, NAI-106, NAI-109, NDI-101, NDI-105, NDI-106, NDI-109, PAI-01, PAI-101, PAI-106, PAI-1001 (all manufactured by Green Chemical Co., Ltd.) ), SP-077, SP-082 (all manufactured by ADEKA Co., Ltd.), TPS-PFBS (all manufactured by Toyo Gosei Kogyo Co., Ltd.), MDT (all manufactured by Heraeus), WPAG-281, WPAG-336, WPAG-339, WPAG-342, WPAG-344, WPAG-350, WPAG-370, WPAG-372, WPAG-449, WPAG-469, WPAG-505, WPAG-506 (all manufactured by Wako Pure Chemical Industries, Ltd.), etc.
[0156] From the viewpoint of increasing the degree of crosslinking of the organic film (C) and further increasing the bending resistance of the resin-coated ultra-thin glass, the content of a curing catalyst such as a thermal acid generator or a photoacid generator in the composition containing the siloxane resin (E) is preferably 0.1% by weight or more, more preferably 0.3% by weight or more in the total solid content. On the other hand, from the viewpoint of the temporal stability of the composition containing the siloxane resin (E), the content of a curing catalyst such as a thermal acid generator or a photoacid generator is preferably 5% by weight or less, more preferably 3% by weight or less in the total solid content.
[0157] The composition containing the siloxane resin (E) may also contain a polymerization inhibitor. By containing a polymerization inhibitor, the stability over time can be improved. Examples of the polymerization inhibitor include phenol, catechol, resorcinol, hydroquinone, 4-tert-butylcatechol, 2,6-di(tert-butyl)-p-cresol, phenothiazine, and 4-methoxyphenol.
[0158] The content of the polymerization inhibitor in the composition containing the siloxane resin (E) is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, based on the total solid content. On the other hand, from the viewpoint of not hindering the crosslinking of the organic film (C), it is preferably 5% by weight or less, more preferably 1% by weight or less, based on the total solid content.
[0159] The composition containing the siloxane resin (E) may also contain an ultraviolet absorber. By containing an ultraviolet absorber, the light resistance of the organic film (C) can be improved. As the ultraviolet absorber, benzotriazole compounds, benzophenone compounds, and triazine compounds can be preferably used in terms of transparency and non-coloring properties.
[0160] Examples of the benzotriazole compound include 2-(2H-benzotriazol-2-yl)phenol, 2-(2H-benzotriazol-2-yl)-4,6-tert-amylphenol, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol, 2(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol, and 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole.
[0161] Examples of the benzophenone-based compound include 2-hydroxy-4-methoxybenzophenone.
[0162] Examples of the triazine compound include 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol.
[0163] From the viewpoint of improving the adhesion between the organic film (C) and the ultrathin glass (A), the content of the ultraviolet absorber in the composition containing the siloxane resin (E) is preferably 10 wt % or less, more preferably 5 wt % or less, based on the total solid content.
[0164] The composition containing the silicone resin (E) may also contain a surfactant. By containing a surfactant, the fluidity during coating can be improved. Examples of surfactants include: fluorine-based surfactants; silicone-based surfactants; fluorine-containing thermally decomposable surfactants; polyether-modified silicone-based surfactants; polyalkylene oxide-based surfactants; poly(meth)acrylate-based surfactants; anionic surfactants such as ammonium lauryl sulfate and polyoxyethylene alkyl ether triethanolamine sulfate; cationic surfactants such as stearylamine acetate and lauryl trimethylammonium chloride; amphoteric surfactants such as lauryl dimethylamine oxide and lauryl carboxyl methyl hydroxyethyl imidazolium betaine; nonionic surfactants such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, and sorbitan monostearate, etc. Two or more of these surfactants may also be contained.
[0165] Among these surfactants, from the viewpoint of suppressing poor coating properties such as dents, reducing surface tension, and suppressing unevenness during coating film drying, preferred are fluorine-based surfactants, silicone-based surfactants, fluorine-containing thermally decomposable surfactants, and polyether-modified siloxane-based surfactants, and more preferred are fluorine-containing thermally decomposable surfactants.
[0166] Examples of commercially available fluorine-based surfactants include: Megafac (registered trademark) F142D, Megafac (registered trademark) F172, Megafac (registered trademark) F173, Megafac (registered trademark) F183, Megafac (registered trademark) F445, Megafac (registered trademark) F470, Megafac (registered trademark) F475, Megafac (registered trademark) F477 (all manufactured by DIC Corporation), NBX-15, and FTX-218 (manufactured by NEOS Corporation). Examples of commercially available silicone surfactants include BYK-333, BYK-301, BYK-331, BYK-345, and BYK-307 (manufactured by BYK-Chemie Japan Co., Ltd.). Examples of commercially available fluorinated thermally decomposable surfactants include Megafac DS-21 (manufactured by DIC Co., Ltd.). Examples of commercially available products of polyether-modified silicone surfactants include: BYK-345, BYK-346, BYK-347, BYK-348, BYK-349 (all manufactured by BYK-Chemie Japan Co., Ltd.), SAG002, SAG005, SAG0503A, and SAG008 (all manufactured by Nissin Chemical Industries, Ltd.).
[0167] Next, a method for producing a composition containing a siloxane resin (E) will be described below.
[0168] The method for producing a composition containing a siloxane resin (E) is generally a method of mixing a predetermined amount of the siloxane resin (E) and other raw materials such as silica particles, a photoradical polymerization initiator, a compound having two or more radical polymerizable groups, and a solvent as required, and stirring.
[0169] Furthermore, an organic film having a hardness different from that of the organic film (B) or the hard coat layer may be formed between the organic film (B) and the hard coat layer.
[0170] The resin-coated ultra-thin glass of the present invention can be preferably used as a cover glass of a display device such as a smartphone or a tablet personal computer (PC), a car display, or an instrument panel by having the organic buffer film (B) on the surface side.
[0171] The surface side refers to a surface that is located on the user's side and can be touched by fingers or the like when the resin-coated ultra-thin plate glass is used as a cover glass on the front side of a display device.
[0172] The back side refers to a side that cannot be touched by a user when the resin-coated ultra-thin plate glass is used as a front cover glass of a display device.
[0173] Example
[0174] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0175] (Evaluation method)
[0176] <Impact resistance>
[0177] OCA (trade name 'OPTERIA (registered trademark) MO-3017; manufactured by Lintec (Co., Ltd.)') with a thickness of 50 μm was attached to the upper side of the organic film (C) side (back side) formed on the ultra-thin plate glass (A). Next, the upper side of the OCA was attached to a plate of stainless steel (SUS) 304 with a thickness of 10 mm, and the ultra-thin plate glass (A) was placed so that the SUS 304 was on the lower side.
[0178] Next, a ballpoint pen weighing 5.7 g and having a core diameter of 0.7 mm was dropped from a predetermined height on the organic film (B) side (surface side) of the ultra-thin plate glass (A) to observe whether the ultra-thin plate glass was cracked. If no cracks were found, the drop height of the ballpoint pen was increased and the same evaluation was performed to measure the minimum height (PT1) of the crack of the ultra-thin plate glass and evaluate according to the following criteria.
[0179] ◎:15≦PT1
[0180] ○:5≦PT1<15
[0181] ×:PT1<5.
[0182] <Bending resistance>
[0183] The number of times (BT1) when the glass or organic film breaks or cracks at a radius of curvature (R) of 2 mm was measured using a durability tester DMLHB (manufactured by Yuasa System Equipment Co., Ltd.) in which the organic film (C) formed on the ultra-thin plate glass (A) was placed on the lower side. The maximum number of tests was 10,000, and the evaluation was performed according to the following criteria.
[0184] ◎: BT1 = 10000 (no breakage or cracks in glass or organic film)
[0185] ○: 1000≦BT1<10000
[0186] ×: BT1<1000.
[0187] <Yellowness of film>
[0188] The organic film (B) described in each of the Examples and Comparative Examples was produced using 0.5 mm thick alkali-free glass instead of the ultra-thin plate glass.
[0189] Regarding the organic film (B) on the alkali-free glass, the transmittance at a measuring wavelength of 380 nm to 780 nm was measured using an ultraviolet-visible spectrophotometer UV-2600 (manufactured by Shimadzu Corporation). Based on the measured transmittance, the yellowness (YI) of the transmitted light under the D65 light source was calculated. It can be said that the smaller the value, the better the yellowness (YI).
[0190] <Pencil hardness>
[0191] The resin-coated glass obtained in each example and comparative example was prepared by using 0.5 mm thick alkali-free glass instead of ultra-thin plate glass. The pencil hardness was measured by drawing on the organic film (B) side (surface side) of the alkali-free glass with a pencil of a specified hardness at a load of 750 g and an angle of 45 degrees using a pencil hardness tester and observing whether there were scratches.
[0192] (Synthesis of Siloxane Resin (PS-1))
[0193] In a 500 mL three-necked flask, 47.67 g (0.35 mol) of methyltrimethoxysilane, 39.66 g (0.20 mol) of phenyltrimethoxysilane, 26.23 g (0.10 mol) of 3-trimethoxysilylpropylsuccinic anhydride, 82.04 g (0.35 mol) of 3-acryloxypropyltrimethoxysilane, and 182.88 g of diacetone alcohol (hereinafter referred to as "DAA") were placed, and the mixture was immersed in a 40° C. oil bath and stirred. At the same time, a phosphoric acid aqueous solution in which 0.391 g (0.2 parts by weight relative to the monomers charged) of phosphoric acid was dissolved in 55.8 g of water was added using a dropping funnel over 10 minutes. After stirring at 40° C. for 1 hour, the oil bath temperature was set to 70° C. and stirred for 1 hour, and the oil bath temperature was further raised to 115° C. over 30 minutes. One hour after the start of heating, the internal temperature of the solution reached 100°C, and then heated and stirred for 2 hours (internal temperature was 100°C to 110°C). During the reaction, a total of 120g of by-products, namely methanol and water, were distilled out. DAA was added to the obtained DAA solution of siloxane resin to make the polymer concentration become 40% by weight, to obtain a siloxane resin (PS-1) solution. Furthermore, the weight average molecular weight (hereinafter referred to as "Mw") of the obtained siloxane resin (PS-1) was measured by gel permeation chromatography (GPC), and the result was 5,000 (polystyrene conversion).
[0194] (Synthesis of Siloxane Resin (PS-2))
[0195] In a 500 mL three-necked flask, 54.48 g (0.40 mol) of methyltrimethoxysilane, 99.15 g (0.50 mol) of phenyltrimethoxysilane, 24.64 g (0.10 mol) of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 163.35 g of DAA were added, immersed in a 40°C oil bath and stirred, and a phosphoric acid aqueous solution in which 0.535 g of phosphoric acid (0.3 parts by weight relative to the monomers added) was dissolved in 54.0 g of water was added using a dropping funnel over a period of 10 minutes. After stirring at 40°C for 1 hour, the oil bath temperature was set to 70°C and stirred for 1 hour, and the oil bath was heated to 115°C over a period of 30 minutes. The internal temperature of the solution reached 100°C 1 hour after the start of the temperature increase, and then heated and stirred for 2 hours (the internal temperature was 100°C to 110°C). During the reaction, a total of 120 g of by-products, namely methanol and water, were distilled out. DAA was added to the obtained DAA solution of siloxane resin so that the polymer concentration became 40 wt % to obtain a siloxane resin (PS-2) solution. Furthermore, the Mw of the obtained siloxane resin (PS-2) was measured by GPC and found to be 5,000 (in terms of polystyrene).
[0196] (Preparation of a composition containing a silicone resin (GR-1))
[0197] Under a yellow light, 1.52 g of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (trade name 'Omnirad (registered trademark) 819'; manufactured by IGM) and 1.30 g of zirconium tetraacetylacetonate (trade name 'Orgatix (registered trademark) ZC-150'; manufactured by Matsumoto Fine Chemical (Co., Ltd.)) were dissolved in a mixed solvent of 23.96 g of DAA, 1.53 g of propylene glycol monomethyl etheracetate (hereinafter referred to as "PGMEA"), and 14.80 g of 3-methyl-3-methoxy-1-butanol (hereinafter referred to as "MMB"), and a siloxane compound having an oxetane group ('Aron oxetane') was added. 0.98 g of oxetane (registered trademark) (OXT-191'; manufactured by Toagosei Co., Ltd.), 0.43 g of 3-aminopropyltrimethoxysilane (trade name "KBM-903"; manufactured by Shin-Etsu Chemical Co., Ltd.), 4.35 g of acrylate of tris(2-hydroxyethyl)isocyanuric acid (trade name 'Aronix (registered trademark)' M-315'; manufactured by Toagosei Co., Ltd.), 28.99 g of a 30 wt% dispersion of silica particles in PGMEA (average particle size = 20 nm to 30 nm, trade name "PMA-ST"; manufactured by Nissan Chemical Co., Ltd.), 21.74 g of a siloxane resin (PS-1) solution, and 0.5 g of a PGMEA dispersion of a fluorinated thermally decomposable surfactant (trade name "DS-21"; manufactured by DIC Corporation). 0.20 g of a 5 wt% solution (equivalent to a concentration of 100 ppm) of 1% ...
[0198] (Preparation of a composition containing a silicone resin (GR-2))
[0199] Under a yellow light, 0.36 g of trifluoromethanesulfonate (trade name "MDT"; manufactured by Heraeus) was dissolved in a mixed solvent of 4.00 g of DAA, 8.80 g of PGMEA, and 22.20 g of 3-methoxy-3-methyl-1-butyl acetate (boiling point = 188° C.), and 0.54 g of a silane-modified isocyanurate compound (trade name "KBM-9659"; manufactured by Shin-Etsu Chemical Co., Ltd.), 23.89 g of a PGMEA 30 wt% dispersion of silica particles (average particle size = 20 nm to 30 nm, trade name "PMA-ST"; manufactured by Nissan Chemical Co., Ltd.), 39.82 g of a siloxane resin (PS-2) solution, and a PGMEA solution of a fluorinated thermally decomposable surfactant (trade name "DS-21"; manufactured by DIC Corporation) were added. 0.20 g of a 5 wt% solution (equivalent to a concentration of 100 ppm) of 1% ...
[0200] (Preparation of Composition (GB-1) Containing Thermoplastic Resin)
[0201] 15.00 g of a thermoplastic polyester resin (trade name 'Vylon (registered trademark) 200'; manufactured by Toyobo Co., Ltd.) (hereinafter referred to as "Vylon 200") and 84.90 g of PGMEA were placed in a 500 mL three-necked flask, immersed in an oil bath at 60°C, and mixed and stirred until Vylon 200 was dissolved. 0.10 g (equivalent to a concentration of 50 ppm) of a 5 wt% PGMEA solution of a fluorinated thermally decomposable surfactant (trade name "DS-21"; manufactured by DIC Co., Ltd.) was added to the obtained Vylon 200 PGMEA solution, and stirred. Then, the mixture was filtered using a 1.00 μm filter to prepare a composition (GB-1) containing a thermoplastic resin having a solid content concentration of 15 wt%.
[0202] (Example 1)
[0203] Using a spray coating device (trade name '"rCoater (registered trademark)" ES1533'; manufactured by Asahi Sunac Co., Ltd.), the composition (GR-1) containing the siloxane resin was spray-coated on one (back side) of the chemically strengthened ultra-thin plate glass (trade name '"Dinorex (registered trademark)" T2X-1'; manufactured by Nippon Electric Glass Co., Ltd.) with a thickness of 50 μm as a substrate, and then pre-baked for 2 minutes using a hot plate at 100°C to obtain a pre-baked film. Then, using an exposure machine "XG-5000" manufactured by Dainippon Screen Co., Ltd., the exposure was performed at 500 mJ / cm 2 The resulting film was exposed (in terms of i-rays) and cured in a hot air oven at 180° C. for 40 minutes to obtain an organic film (C-1) having a film thickness of 5 μm.
[0204] Next, a spray coating device was used to spray-coat the composition (GB-1) containing a thermoplastic resin on the side (surface side) of the ultra-thin plate glass where the organic film (C-1) was not formed, and then pre-baked for 6 minutes using a 90°C hot plate to obtain a pre-baked film. Next, a hot air oven at 210°C was used to cure for 40 minutes to obtain an organic film (B-1) with a film thickness of 20 μm.
[0205] Next, a hard coating material (trade name '"lioduras (registered trademark)" LCH2391'; manufactured by Toyo Chem (Co., Ltd.)) was spray-coated on the organic film (B-1), and then pre-baked for 1 minute using a hot plate at 80°C to obtain a pre-baked film. Then, 1500mJ exposure was performed using an exposure machine "UVC-1212S1WF01" manufactured by USHIO (Co., Ltd.) to prepare a 7μm hard coating (H-1), thereby obtaining a resin-coated ultra-thin plate glass (SG-1). The results of the evaluation by the above method are shown in Table 2.
[0206] (Example 2)
[0207] A resin-coated ultra-thin plate glass (SG-2) was prepared in the same manner as in Example 1 except that the hard coat layer was not formed. Table 2 shows the results of the evaluation by the above method.
[0208] (Example 3)
[0209] A resin-coated ultra-thin glass plate (SG-3) was prepared in the same manner as in Example 1 except that a composition containing a siloxane resin (GR-2) was used to prepare an organic film (C-2) having a film thickness of 5 μm. Table 2 shows the results of the evaluation by the above method.
[0210] (Example 4)
[0211] By adjusting the spraying speed and the ejection amount when making the organic film (B-1), an organic film (B-2) with a film thickness of 40 μm was obtained. Except for changing the film thickness of the organic film (B-1), a resin-coated ultra-thin plate glass (SG-4) was made in the same manner as in Example 1. The results of the evaluation by the above method are shown in Table 2.
[0212] (Example 5)
[0213] A composition (GB-2) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was replaced with a thermoplastic polyester resin (trade name '"Vylon (registered trademark)" 600'; manufactured by Toyobo Co., Ltd.).
[0214] A resin-coated ultra-thin plate glass (SG-5) was produced in the same manner as in Example 1 except that the obtained GB-2 was used to produce the organic film (B-3). Table 2 shows the results of the evaluation by the above method.
[0215] (Example 6)
[0216] A composition (GB-3) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was replaced with a vinyl chloride-vinyl acetate copolymer resin (trade name 'SOLBIN (registered trademark)' TA-5R'; manufactured by Nissin Chemical Industry Co., Ltd.).
[0217] A resin-coated ultra-thin plate glass (SG-6) was prepared in the same manner as in Example 1 except that the obtained GB-3 was used to prepare the organic film (B-4). Table 2 shows the results of the evaluation by the above method.
[0218] (Example 7)
[0219] A composition (GB-4) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was replaced with a (meth)acrylate resin (trade name '"Hi-pearl (registered trademark)" M-4006'; manufactured by Negami Industries Co., Ltd.).
[0220] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-4 was used to produce the organic film (B-5).
[0221] (Example 8)
[0222] A composition (GB-6) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was replaced with a thermoplastic polyester resin (trade name '"Vylon (registered trademark)" GK-360'; manufactured by Toyobo Co., Ltd.).
[0223] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-6 was used to produce the organic film (B-8).
[0224] (Example 9)
[0225] A composition (GB-7) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was replaced with a thermoplastic polyester resin (trade name '"Vylon (registered trademark)" 270'; manufactured by Toyobo Co., Ltd.).
[0226] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-7 was used to produce the organic film (B-9).
[0227] (Example 10)
[0228] A composition (GB-8) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was replaced with a thermoplastic polyester resin (trade name '"Vylon (registered trademark)" GK-880'; manufactured by Toyobo Co., Ltd.).
[0229] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-8 was used to produce the organic film (B-10).
[0230] (Example 11)
[0231] A composition (GB-9) containing a thermoplastic resin was prepared in the same manner as GB-1, except that Vylon 200 was changed to 13.50 g and thermosetting urethane acrylate (trade name 'NK Oligo (registered trademark)' U-6LPA'; manufactured by Shin-Nakamura Chemical Co., Ltd.) (double bond equivalent: 127 g / mol) (hereinafter referred to as "U-6LPA") was changed to 1.50 g.
[0232] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-9 was used to produce the organic film (B-11).
[0233] (Example 12)
[0234] A resin-coated ultra-thin glass plate (SG-16) was prepared in the same manner as in Example 11 except that the hard coat layer was not formed. Table 2 shows the results of the evaluation by the above method.
[0235] (Example 13)
[0236] A composition (GB-10) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was changed to 12.00 g and U-6LPA was changed to 3.00 g.
[0237] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-10 was used to produce the organic film (B-12).
[0238] (Example 14)
[0239] A composition (GB-11) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was changed to 10.50 g and U-6LPA was changed to 4.50 g.
[0240] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-11 was used to produce the organic film (B-13).
[0241] (Example 15)
[0242] A composition (GB-12) containing a thermoplastic resin was prepared in the same manner as GB-9 except that U-6LPA was replaced with thermosetting urethane acrylate (trade name 'NK Oligo (registered trademark)' UA-122P'; manufactured by Shin-Nakamura Chemical Co., Ltd.) (double bond equivalent: 550 g / mol).
[0243] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-12 was used to produce the organic film (B-14).
[0244] (Example 16)
[0245] A composition (GB-13) containing a thermoplastic resin was prepared in the same manner as GB-9 except that U-6LPA was replaced with thermosetting urethane acrylate (trade name 'NK Oligo (registered trademark)' U-2HA'; manufactured by Shin-Nakamura Chemical Co., Ltd.) (double bond equivalent: 200 g / mol).
[0246] The results of the evaluation by the above method are shown in Table 2, except that the obtained GB-13 was used to produce the organic film (B-15).
[0247] (Comparative Example 1)
[0248] Table 2 shows the results of evaluation by the above-mentioned method on ultra-thin glass sheets on which the organic film (B), the organic film (C) and the hard coating layer were not formed.
[0249] (Comparative Example 2)
[0250] A resin-coated ultra-thin glass plate (SG-8) was prepared in the same manner as in Example 1 except that the organic film (B-1) was not formed. Table 2 shows the results of the evaluation by the above method.
[0251] (Comparative Example 3)
[0252] By the same method as the organic film (C-1), an organic film (B-6) containing a composition (GR-1) of a siloxane resin with a film thickness of 5 μm was prepared on the surface side of the ultra-thin plate glass. Except for B-6, a resin-coated ultra-thin plate glass (SG-9) was prepared in the same manner as in Example 1. The results of the evaluation by the above method are shown in Table 2.
[0253] (Comparative Example 4)
[0254] A resin-coated ultra-thin glass plate (SG-10) was prepared in the same manner as in Example 1 except that the organic film (C-1) was not formed. Table 2 shows the results of the evaluation by the above method.
[0255] (Comparative Example 5)
[0256] A composition (GB-5) containing a thermoplastic resin was prepared in the same manner as GB-1 except that Vylon 200 was replaced with a (meth)acrylate resin (trade name 'Optimus 7500'; manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0257] A resin-coated ultra-thin plate glass (SG-11) was produced in the same manner as in Example 1 except that the obtained GB-5 was used to produce an organic film (B-7). Table 2 shows the results of the evaluation by the above method.
[0258] [Table 1]
[0259]
[0260]
[0261]
[0262] Industrial Applicability
[0263] The resin-coated ultra-thin plate glass of the present invention has high impact resistance, good bending resistance, and high transparency, and therefore can be used as a cover glass for a flexible display device.
Claims
1. A resin-coated ultra-thin plate glass, comprising three layers: an organic film B formed on one side of an ultra-thin plate glass A having a thickness of 10 μm or more and 100 μm or less, and an organic film C formed on the other side, wherein in the resin-coated ultra-thin plate glass, the organic film B is formed of a composition containing a thermoplastic resin D having a weight average molecular weight of 10,000 to 70,000, and the organic film C is formed of a composition containing a siloxane resin E, The thickness of the organic film B is greater than 10 μm and less than 100 μm, the thickness of the organic film C is greater than 1 μm and less than 20 μm, and the thermoplastic resin D is one or more of polyester resin, (meth)acrylate resin, polyester urethane resin, urethane resin, silicone resin, cellulose resin, polyolefin resin, epoxy resin, and vinyl chloride-vinyl acetate copolymer resin.
2. The resin-coated ultra-thin glass according to claim 1, wherein: The organic film B is a buffer film b, the organic film C is a strengthening film c, and the ultra-thin plate glass A has a thickness of 20 μm or more and 100 μm or less.
3. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: The content of the phenyl groups in the siloxane resin E is 5 mol % to 60 mol % relative to Si atoms.
4. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: The glass transition temperature of the thermoplastic resin D is 40°C to 110°C.
5. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: The thermoplastic resin D is a polyester resin or a (meth)acrylate resin.
6. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: The organic film B contains a thermosetting resin.
7. The resin-coated ultra-thin glass according to claim 6, wherein: The thermosetting resin is a urethane (meth) acrylate compound.
8. The resin-coated ultra-thin glass according to claim 7, wherein: The organic film B contains 5 to 35 wt % of the urethane (meth)acrylate compound in the total solid content.
9. The resin-coated ultra-thin glass according to claim 7 or 8, wherein: The double bond equivalent of the urethane (meth)acrylate is 100 g / mol to 600 g / mol.
10. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: The yellowness YI of the organic film B is |YI|<20.
11. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: The siloxane resin E has a radical polymerizable group.
12. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: The ultra-thin plate glass A is chemically strengthened.
13. The resin-coated ultra-thin glass according to claim 1 or 2, wherein: A hard coating layer is laminated on the surface of the organic film B that is not on the ultra-thin plate glass A side. 14 . A flexible display device, comprising the resin-coated ultra-thin plate glass according to claim 1 , wherein the organic film B is disposed on the surface side.
Citation Information
Patent Citations
Polymer coated glass thin film substrate
JP2002542971A
Glass protection film forming composition and glass protection film
JP2016003160A
composite
WO2015194324A1
Laminate and display device
JP2005014563A
Glass reinforced substrate
JP2019214492A